2014
DOI: 10.4103/1119-3077.130229
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of burnout among health workers and bankers in Aba south local government area, Abia state, South East Nigeria

Abstract: The prevalence of burnout risk among health workers and bankers is high. More female health workers are at risk of burnout than male health workers. There should be policies aimed at identifying those most at risk and reducing the prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…There are no differences in work stress level regarding the gender and age of the participants which is consistent with some other research results [17,24,25,16].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…There are no differences in work stress level regarding the gender and age of the participants which is consistent with some other research results [17,24,25,16].…”
Section: Discussionsupporting
confidence: 81%
“…Aguwa, Nduka & Arinze-Onyia [24] did a research regarding demographic variables and found that female health workers and workers with lower education are at more risk of burnout than male health workers and workers with higher education. However, age, marital status and years of work did not significantly affect burnout score.…”
Section: Introductionmentioning
confidence: 99%
“…[18] The finding here that depression is more common among the female gender, which was significant, agrees with other studies that have shown depression and depressive symptoms to be more prevalent in the female gender. [1,3,4,[18][19][20][21] Some other studies find that mental disorders in general, depression included, occur more in women, [13] while some others show men with a greater prevalence. [5,17] No difference in the prevalence of depression between men and women has also been reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of previous research on this aspect are not clear-cut: some studies found that single people were more susceptible to burnout (26,38) while others found no significant association (39,40).…”
Section: Discussionmentioning
confidence: 94%